Recovery of severe muscular and fascial calcinosis after treatment with bisphosphonates in a child with juvenile dermatomyositis (2015)
Abstract: Juvenile dermatomyositis (JDM) is a serious systemic autoimmune condition primarily affecting proximal muscles and skin, which is frequently associated with calcinosis. We report a case of a 10-year-old boy with JDM and severe calcification deposits along fasciae and muscle planes. He complained of symptoms associated to JDM with pulmonary involvement since 1 year before receiving medical attention. Three months before consultation, he experienced bilateral leg pain accompanied by progressive hardening of muscles and the presence of small nodules around the elbows and submandibular region. Computed tomography images revealed a severe “eggshell” calcification pattern of the lower-limb muscular fasciae. Significant clinical and radiological improvement was achieved after 30 months of alendronate therapy